The possibilities and potential of a pedagogical partnership between university and community-based initial teacher educators for LGBTQ+ specific inclusion and diversity - Murphy, Gavin; Ní Dhuinn, Melanie (Frontiers in Education, 2022)
In this study, we explore the possibilities and potential of a pedagogical partnership between university and community-based initial teacher educators for LGBTQ+-specific inclusion and diversity. We map and discuss important initial teacher education (ITE) and broader inclusion and diversity policy contexts relevant to this pedagogical innovation as part of an Sociology of Education module. We describe and conceptually frame the innovation as equity, social justice, inclusion and diversity focused, and as rooted in democratic ITE reform. We then explore its impact on student teachers by drawing on the discussion board posts and reflections required as part of the module. Based on our findings, we offer ITE system-focused, ITE programmatic and personal reflections as teacher educators to conclude in considering how such pedagogical partnerships and innovations can enhance ITE for inclusion and diversity and, fundamentally, in pursuing more democratic schools and society.